Bacterial diversity analysis of Xiangpai brined beef based on high-throughput sequencing - CHE Li-na; ZHAO Liang-zhong; ZHOU Xiao-jie (Shipin yu jixie, 2023)
Objective: This study aimed to preserve the flavor of Xiangpai brined beef and prolong its shelf life. Methods: High-throughput sequencing was performed in Xiangpai brined beef samples with different storage time (0, 4, 8, 12, 16 d). Results: A total of 1 116 813 effective gene sequence bands were obtained, with an average of 74 454 bands per sample. Alpha diversity analysis showed that LNR8d had the highest bacterial abundance, while LNR4d had the lowest bacterial abundance. The results showed that during storage, Firmicutes, Proteobacteria and Cyanobacteria were dominant bacteria in the 15 brined beef samples. Bacillus was the dominant bacterium in LNR0d samples, while the dominant bacterium in LNR4d samples was Macrococcus. The dominant bacterium in LNR8d samples was Enterobacter. The dominant bacteria in LNR12d samples also belonged to Bacillus, and the dominant bacterium in LNR16d samples was Unidentified chloroplast. PCA analysis showed that the distance between the 15 samples within the group was large, indicating that the microbiota diversity of the 15 samples varied greatly. LEfSe analysis showed that in LNR4d ~ LNR16d samples, the bacteria with the largest contribution at the genus level were Macrococcus, Microbacillus and Lactobacillus. Conclusion: This study revealed the diversity of bacteria in the storage process of Xiangpai braised beef and explored the changes of bacteria and its dominant bacteria genus during the storage process.